New labor in New York : precarious workers and the future of the labor movement - Milkman, Ruth, 1954-; Ott, Ed (ILR Press, an imprint of Cornell University Press, 2014)
New York City boasts a higher rate of unionization than any other major U.S. city, roughly double the national average, but the city's unions have suffered steady and relentless decline, especially in the private sector. With higher levels of income inequality than any other large city in the nation, New York today is home to a large and growing "precariat": workers with little or no employment security who are often excluded from the basic legal protections that unions struggled for and won in the twentieth century.